Camus and Sartre, ¿contrast or philosophicalaffinity? Conceptions about the idea of existentialresponsibility - Ramírez Agüero, Byron (2024)
This essay is based on the question: how to represent the argumentative contrast of the concept of responsibility in the philosophical postulates from Jean-Paul Sartre and Albert Camus?The main objective of this study is to link the way in which bothauthors address, agree, and differ on various philosophical pointsof view about this idea (individual and social human responsibility) throughout their works, and to compare this contrast tothe disputes they have during their life, looking for establishconnections and differences between both philosophical positions (Existentialism and Absurdism), as well as to approach to the foundations of their ideas. This study is based on Sartre byhimself (1955) and The Existentialism is a Humanism (1946),by Sartre, and The Myth of Sisyphus (1942) and The Revel Man (1951) by Camus.